Peran Pemangku Kepentingan (Stakeholders) dalam Pemberdayaan Petani Gurem di Kecamatan Kotabumi Utara, Kabupaten Lampung Utara - Romadhona, Salsabilla Noviya; Listiana, Indah; Ibnu, Muhammad; Gitosaputro, Sumaryo (Fakultas Pertanian, Universitas Lampung, 2025)
The purpose of this study was to to analyze the role of stakeholders in empowering smallholder farmers in Kotabumi Utara District, North Lampung Regency. The research used a qualitative descriptive approach with data collected through observation, interviews, and documentation. The findings indicate that the empowerment activities involve various stakeholders such as village governments, agricultural extension workers, universities, MSMEs, and farmer groups. Empowerment is carried out through training, counseling, institutional strengthening, and development of farming businesses. However, challenges remain, including limited capital, weak community response, and low education levels of smallholder farmers. Therefore, stronger synergy among stakeholders is needed to support sustainable empowerment of smallholder farmers.